2023
DOI: 10.3390/nu15071609
|View full text |Cite
|
Sign up to set email alerts
|

Longevity-Associated Core Gut Microbiota Mining and Effect of Mediated Probiotic Combinations on Aging Mice: Case Study of a Long-Lived Population in Guangxi, China

Abstract: With an ageing population, healthy longevity is becoming an important scientific concern. The longevity phenomenon is closely related to the intestinal microflora and is highly complicated; it is challenging to identify and define the core gut microbiota associated with longevity. Therefore, in this study, 16S rRNA sequencing data were obtained from a total of 135 faecal samples collected as part of the latest sampling and pre-collection initiative in the Guangxi longevity area, and weighted gene co-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…However, this contradicts previous reports of Bacteroides enrichment in long-lived elderly individuals. (Park et al 2015b ; Li et al 2023 ; Pang et al 2023 ). Bacteroides are crucial microorganisms in the human intestine.…”
Section: Discussionmentioning
confidence: 99%
“…However, this contradicts previous reports of Bacteroides enrichment in long-lived elderly individuals. (Park et al 2015b ; Li et al 2023 ; Pang et al 2023 ). Bacteroides are crucial microorganisms in the human intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the gut microbiome, host genetics, and asthma, Li et al, described that, through a two-sample Mendelian randomization analysis, they predicted a positive correlation between the gut species Barnesiella and RuminococcaceaeUCG014 genera and the risk of asthma. Furthermore, they found that Akkermansia reduced the risk of adult-onset asthma ( Li et al, 2023 ). Perez-Garcia et al, through a study of microbiome- genome wide association (mbGWAS) and microbiome quantitative trait loci (mbQTL) analysis, reported the identification of polymorphisms in the APOBEC3B-APOBEC3c, TRIM24, and TPST2 genes that are associated with asthma comorbidities.…”
Section: Microbiome and Asthma: The Importance Of The Beginningmentioning
confidence: 99%
“…Several studies have shown that the use of antibiotics in early childhood increases the risk for developing asthma up to 2.3 times ( Kim et al, 2018 ; Lin et al, 2020 ; Li et al, 2023 ), these risks increase even more with the number of antibiotics courses prescribed. In infants (<1 year) antibiotic use is associated with a 24% higher incidence of asthma for every 10% increase in prescriptions ( Patrick et al, 2020 ).…”
Section: Infancy and Childhood Imprint Developmentmentioning
confidence: 99%
See 2 more Smart Citations